The axioms of flight : The rules of thumb for pilots - Embree, James (Flight Information Publications, 1984)
Takeoff performance - Light twin aircraft - Climb performance - Weight and balance - Airspreed calculations - Time, speed, distance, duel consumption, specific range and endurance - Cruise control - Maneuvering flight - Navigation - Electronic navigation - Descent and approach - Landing performance - Conversions and miscellaneous - Glossary - Appendix.